The allelopathic potential of red macroalga Pyropia haitanensis solvent extracts on controlling bloom-forming microalgae: Insights into the inhibitory compounds - Vishal Patil; Lu Huang; Junrong Liang; Lin Sun; Dazhi Wang; Yahui Gao; Changping Chen (Ecotoxicology and Environmental Safety, 2024)
Various strategies have been explored to mitigate the impact of harmful algal blooms (HABs). While chemical and physical methods have traditionally been employed to regulate microalgal growth, their prolonged adverse effects on the ecosystem are a cause for concern. Recognizing the integral role of macroalgae within the ecosystem, this study reveals the anti-algal properties of solvent-based extracts derived from the red macroalga Pyropia haitanensis as a means of preventing microalgal blooms. In our investigation, we initially assessed the growth-inhibitory effects of methanol and acetone extracts from P. haitanensis on five microalgae known to contribute to bloom-formation. Significantly reduced growth was observed in all microalgal species when inoculated with both methanol and acetone extracts. Further analysis revealed the effectiveness of the methanol extract (ME), and further fractionation with petroleum ether (PE), ethyl acetate (EA), and n-butanol (NB) for testing against Skeletonema costatum and Pseudo-nitzschia pungens. The methanol fractions exhibited strong inhibition, resulting in the complete elimination of both microalgae after 96 hours of exposure to PE, EA, and NB extracts. Gas Chromatography-Mass Spectroscopy (GC-MS) analysis of the ME and its solvent fractions identified 49 confirmed compounds. These compounds are likely potential contributors to the observed inhibition of microalgal growth. In conclusion, our findings suggest that solvent extracts from P. haitanensis possess substantial potential for the control of HABs, offering a promising avenue for further research and application in ecosystem management.